Respuesta :

Answer:

i think the answer is b

Step-by-step explanation:

Answer: for 6(x + 2) - x = 4(x + 4) + 7, x = 11

For 0.8x + 5 = 0.2(40 - x), x = 3

For x = 3

For 5(x - 1) - 6x = - 11x

x = 1/2

Step-by-step explanation:

1)Looking at the first equation,

6(x + 2) - x = 4(x + 4) + 7

6x + 12 - x = 4x + 16 + 7

6x - x - 4x = 16 + 7 - 12

x = 11

2) 0.8x + 5 = 0.2(40 - x)

0.8x + 5 = 8 - 0.2x

Adding 0.2x to the left hand side and the right hand side of the equation, it becomes

0.8x + 0.2x + 5 = 8 - 0.2x + 0.2x

x + 5 = 8

x = 8 - 5 = 3

3) 5(x - 1) - 6x = - 11x

5x - 5 - 6x = - 11x

5x - 6x = - 11x + 5

- x + 11x = 5

10x = 5

x = 5/10 = 1/2

ACCESS MORE